Literasi tentang Kepatuhan Pajak bagi Mahasiswa dan Masyarakat Umum - Ka Tiong; Dharmendra; Ferieka, Hendrieta; Ismaya, Agus; Taqi, Muhamad; Muchlish, Munawar Muchlish (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2023)
Taxes are a source of funds for the government in order to carry out development that comes from the community. Through taxes, the government can regulate economic activities. As a phenomenon that exists in society, tax can be approached from various aspects, for example from sociology, politics, economics, law, and so on. This approach from different aspects gives a certain style to taxes. Meanwhile, from a microeconomic perspective, taxes can be seen as something that is burdensome, something that can reduce people's ability or purchasing power. So if you look at it from just this side, tax can be seen as something that is unprofitable, and something that is unprofitable usually encourages efforts to avoid it.